A tudor domain protein, SIMR-1, promotes siRNA production at piRNA-targeted mRNAs in C. elegans - Kevin I Manage; Alicia K Rogers; Dylan C Wallis; Celja J Uebel; Dorian C Anderson; Dieu An H Nguyen; Katerina Arca; Kristen C Brown; Ricardo J Cordeiro Rodrigues; Bruno FM de Albuquerque; René F Ketting; Taiowa A Montgomery; et al. (eLife, 2020)
piRNAs play a critical role in the regulation of transposons and other germline genes. In Caenorhabditis elegans, regulation of piRNA target genes is mediated by the mutator complex, which synthesizes high levels of siRNAs through the activity of an RNA-dependent RNA polymerase. However, the steps between mRNA recognition by the piRNA pathway and siRNA amplification by the mutator complex are unknown. Here, we identify the Tudor domain protein, SIMR-1, as acting downstream of piRNA production and upstream of mutator complex-dependent siRNA biogenesis. Interestingly, SIMR-1 also localizes to distinct subcellular foci adjacent to P granules and Mutator foci, two phase-separated condensates that are the sites of piRNA-dependent mRNA recognition and mutator complex-dependent siRNA amplification, respectively. Thus, our data suggests a role for multiple perinuclear condensates in organizing the piRNA pathway and promoting mRNA regulation by the mutator complex.